2017
DOI: 10.1016/j.eatbeh.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of weight-related quality of life among individuals with binge eating disorder before and after cognitive behavioral therapy

Abstract: Individuals with obesity and binge eating disorder (BED) report poorer weight-realted quality of life (WRQOL) compared to individuals with obesity alone. Cognitive behavioral therapy (CBT), the best available treatment for BED, does not consistently produce weight loss or improvements in weight QOL. The purpose of the current study was to examine baseline and longitudinal associations between eating-related and psychosocial variables and dimensions of weight QOL. We examined associations between predictor vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…We found evidence for convergent validity obtaining correlations between the IWQOL-Lite subscales and BMI, in line with the results from previous studies (Acevedo & Cepeda, 2009;Bolado-García et al 2008;Kolotkin et al, 2019;Mason et al, 2017). As expected, participants with the higher BMI indicated higher IWQOL levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found evidence for convergent validity obtaining correlations between the IWQOL-Lite subscales and BMI, in line with the results from previous studies (Acevedo & Cepeda, 2009;Bolado-García et al 2008;Kolotkin et al, 2019;Mason et al, 2017). As expected, participants with the higher BMI indicated higher IWQOL levels.…”
Section: Discussionsupporting
confidence: 91%
“…When exploring gender differences, there was a general tendency for women to report higher levels of IWQOL vs. men across all subscales, with the difference being most prominent for Self-Esteem. This association has been reported not only for the IWQOL by Kolotkin and Crosby (2002) and Mason et al (2017), but also in studies with other instruments like the Brief Stigmatizing Situations Inventory, a ten-item self-report that assesses lifetime experiences of weight-related stigma (Sattler, Deane, Tapsell, & Kelly, 2018). In Mexico, women face and internalize discrimination in different domains of life (Organization for Economic Co-operation and Development, 2017), so perceiving stronger impact of weight on quality of life adds more complexity to the structural problem of gender inequality.…”
Section: Discussionsupporting
confidence: 69%
“…This study utilized a prospective design, but it is important to note that the reported associations of post‐surgical LOC eating and global EDE score with weight and mental HRQOL do not prove a causal relationship. While there is evidence that binge eating may be a marker of quality of life impairment in adolescents with obesity (Ranzenhofer et al, ), and those changes in eating disorder‐related symptoms predict improved weight‐related quality of life following treatment for BED (Mason et al, ), the relationships between eating disorder psychopathology and, weight and HRQOL changes following weight loss treatment are not yet fully understood. It is possible that the associations are bidirectional, with eating pathology both resulting from and contributing to unfavorable weight and mental HRQOL outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggest that binge eating serves an affect regulation function. Using EMA, Engelberg, Steiger, Gauvin, and Wonderlich (2007) and Mason et al (2017) found that momentary negative affect and dissociation predicted binge eating across the day. Building on this, Berg et al (2013) and Schaefer et al (2020) found using EMA that guilt steadily increased before and declined after episodes.…”
Section: Lived Experience Of Sbesmentioning
confidence: 99%